Health literacy of students. Results of an online survey at the Bochum health university (Germany) / Gesundheitskompetenz Studierender - Ergebnisse einer Online-Befragung an der Hochschule für Gesundheit Bochum - Reick Sibylle; Hering Thomas (Sciendo, 2018)
Health literacy is of growing importance in public health research in Germany. People with good health literacy are likely to make better health decisions. A large proportion of the German population, not just vulnerable groups, has a problematic or insufficient health literacy.